Characterizing Mars's Magnetotail Topology With Respect to the Upstream Interplanetary Magnetic Fields. Issue 3 (28th February 2020) - Xu, Shaosui; Mitchell, David L.; Weber, Tristan; Brain, David A.; Luhmann, Janet G.; Dong, Chuanfei; Curry, Shannon M.; Ma, Yingjuan; DiBraccio, Gina A.; Halekas, Jasper; Dong, Yaxue; Mazelle, Christian
Abstract: The canonical picture of the magnetotail of unmagnetized planets consists of draped interplanetary magnetic fields (IMFs) forming opposite‐directed lobes, separated by the current sheet. DiBraccio et al. (2018, https://doi.org/10.1029/2018GL077251 ) showed that Mars's magnetotail has a twist departing from this picture. Magnetohydrodynamic (MHD) results suggest that the asymmetry in how open field lines connected to the planet populate the tail causes the apparent twist. To validate this interpretation, we compare the tail topology determined from MHD simulations to that inferred from data collected by the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft, in particular, how each topology responds to the upstream IMF orientation. The occurrence rates for open topology from both data and MHD vary with IMF polarities in a similar fashion as the tail twisting. This suggests that Mars's crustal fields have a global effect on the magnetosphere configuration, supporting the picture of a "hybrid" magnetotail that is partly induced/draped and partly intrinsic/planetary in origin. Plain Language Summary: The interaction of the solar wind with unmagnetized planets, such as Venus, results in an induced magnetotail, which is formed by the interplanetary magnetic field lines draping around the planet, forming opposite‐directed lobes. Mars is similar to Venus in many aspects and was thought to have a similar tail configuration. A recent study, however, shows that Mars has a twist in its tail lobes and that modeling results suggest this twist is caused by the effects of its crustal magnetism. In this study, we use the superthermal electron measurements from MAVEN to infer the magnetotail topology resulting from the interaction between the solar magnetic fields and Mars's crustal fields, which is compared with the global magnetohydrodynamic model topology. Our results support the hypothesis that magnetic reconnection between crustal magnetic sources and the solar wind is responsible for the observed twist in Mars's tail lobes. Key Points: This study provides a detailed mapping of tail magnetic topology at Mars, which is dominated by draped and open magnetic field lines Both the MHD model and data show significant changes in Martian tail topology with respect to east/west IMFs It implies that Mars's crustal fields have a global effect on the magnetosphere configuration, supporting the picture of a hybrid magnetotail